The efficacy of computer-enabled discharge communication interventions: a systematic review. Issue 5 (24th January 2011) - Motamedi, Soror Mona; Posadas-Calleja, Juan; Straus, Sharon; Bates, David W; Lorenzetti, Diane L; Baylis, Barry; Gilmour, Janet; Kimpton, Shandra; Ghali, William A
Abstract : Context: Traditional manual/dictated discharge summaries are inaccurate, inconsistent and untimely. Computer-enabled discharge communications may improve information transfer by providing a standardised document that immediately links acute and community healthcare providers. Objective: To conduct a systematic review evaluating the efficacy of computer-enabled discharge communication compared with traditional communication for patients discharged from acute care hospitals. Data sources: MEDLINE, EMBASE, Cochrane CENTRAL Register of Controlled Trials and MEDLINE In-Process. Keywords from three themes were combined: discharge communication, electronic/online/web-based and controlled interventional studies. Study selection: Study types included: clinical trials, quasiexperimental studies with concurrent controls and controlled before–after studies. Interventions included: (1) automatic population of a discharge document by computer database(s); (2) transmission of discharge information via computer technology; or (3) computer technology providing a 'platform' for dynamic discharge communication. Controls included: no intervention or traditional manual/dictated discharge summaries. Primary outcomes included: mortality, readmission and adverse events/near misses. Secondary outcomes included: timeliness, accuracy, quality/completeness and physician/patient satisfaction. Data extraction: Description of interventions and study outcomes were extracted by two independent reviewers. Results: 12 unique studies were identified: eight randomised controlled trials and four quasi-experimental studies. Pooling/meta-analysis was not possible, given the heterogeneity of measures and outcomes reported. The primary outcomes of mortality and readmission were inconsistently reported. There was no significant difference in mortality, and one study reported reduced long-term readmission. Intervention groups experienced reductions in perceived medical errors/adverse events, and improvements in timeliness and physician/patient satisfaction. Conclusions: Computer-enabled discharge communications appear beneficial with respect to a number of important secondary outcomes. Primary outcomes of mortality and readmission are less commonly reported in this literature and require further study.